Disseminated toxoplasmosis after hematopoietic stem cell transplantation showing unusual magnetic resonance images. Issue 4 (20th June 2017) - Tateno, Takahiro; Onozawa, Masahiro; Hashiguchi, Junichi; Ishio, Takashi; Yuzawa, Sayaka; Matsuoka, Satomi; Kosugi‐Kanaya, Mizuha; Okada, Kohei; Shiratori, Souichi; Goto, Hideki; Kimura, Taichi; Sugita, Junichi; et al.
Abstract: We herein report a patient who had disseminated toxoplasmosis after hematopoietic stem cell transplantation showing atypical clinical presentation and neuroimaging. Parkinsonism symptoms such as muscle rigidity, bradykinesia, tremor, and postural instability were initial manifestations. Magnetic resonance imaging showed diffuse symmetrical lesions of bilateral basal ganglia lacking ringed enhancement. Post‐mortem analysis revealed multiple tachyzoites of Toxoplasma gondii in the basal ganglia, mid brain, cerebellum, and cardiac muscle.